2018
DOI: 10.1111/nph.15534
|View full text |Cite
|
Sign up to set email alerts
|

TIRNBLRR immune receptor SOC3 pairs with truncated TIRNB protein CHS1 or TN2 to monitor the homeostasis of E3 ligase SAUL1

Abstract: Summary Intracellular nucleotide binding (NB) and leucine‐rich repeat (NLR) proteins function as immune receptors to recognize effectors from pathogens. They often guard host proteins that are the direct targets of those effectors. Recent findings have revealed that a typical NLR sometimes cooperates with another atypical NLR for effector recognition. Here, by using the CRISPR/Cas9 gene editing method, knockout analysis and biochemical assays, we uncovered differential pairings of typical Toll Interleukin1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…SOC3 can partner with either of the genetically linked CHS1 or TN2 to monitor the homeostasis of E3 ligase SAUL1. SOC3 appears to be the executor module [18,19].…”
Section: Sensor Nlrsmentioning
confidence: 99%
“…SOC3 can partner with either of the genetically linked CHS1 or TN2 to monitor the homeostasis of E3 ligase SAUL1. SOC3 appears to be the executor module [18,19].…”
Section: Sensor Nlrsmentioning
confidence: 99%
“…At present, CRISPR-Cas has multiplex editing capability, that is, it edits more than one gene at a time 38 . In addition, CRISPR-Cas can target not only the open reading frame (ORF) 39 and untranslated region 40 of one coding gene but also non-coding RNAs (ncRNAs) including long ncRNA 41 and microRNA 42 , as well as promoter regions 43 . Single-base substitutions at genomic targets without requiring DSBs have also been achieved 44 .…”
Section: Genome Editing Has Been Revolutionized By the Development Ofmentioning
confidence: 99%
“…Arabidopsis senescence-associated E3 ubiquitin ligase 1 (SAUL1) was initially identified as a U-box E3 ubiquitin ligase required for the suppression of premature senescence [ 19 ]. Recently, it has been shown that a loss-of-function mutation in SAUL1 results in enhanced disease resistance against multiple biotrophic pathogens [ 20 , 21 , 22 , 23 , 24 ]. This autoimmunity is totally dependent on Enhanced Disease Susceptibility 1 (EDS1), Phytoalexin Deficient 4 (PAD4), and Suppressor of the G2 Allele of SKP1b (SGT1B) [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A level of SAUL1 exceeding a certain threshold range will lead to the activation of immunity. Liang et al recently uncovered SOC3 pairs with different truncated TIR-NB (TN) proteins to monitor either the absence or overexpression of SAUL1, respectively [ 24 ].…”
Section: Introductionmentioning
confidence: 99%